An Approach Of Multipath Routing For Congestion Control Improvement In Manet (International Journal of Scientific Research and Management (IJSRM), 2015)
MANET is mobile ad hoc network that consists of mobile platforms which are free to move arbitrarily. Due to dynamic exchange of data among mobile nodes, the paths connecting source nodes with destination nodes are very unstable and may go down at any time. There are a number of issues and challenges faced in MANETs but routing is a main factor considered among all the issues. MANET nodes have limited power and transmission capacity, they intercommunicate by multi hop relay. Multi hop routing have many challenges such as limited wireless bandwidth, low device power, dynamically changing network topology, and high vulnerability to failure. To answer those challenges, many routing algorithms in MANETs were proposed. But one of the problems in routing algorithm is congestion which decreases the overall performance of the network so in this paper we are trying to identify the best routing algorithm which will improve the congestion control mechanism in MANET.